Sistem Informasi Akademik Sekolah Dasar Al-Muhajirin Barehan Sidoharjo Pacitan - Dwi Sugiarti - Fakultas Teknologi Informatika Universitas Surakarta; Indah Uly Wardati -Fakultas Teknologi Informatika Universitas Surakarta (SPEED - Sentra Penelitian Engineering dan Edukasi, 2017)
ABSTRACT: In this time as according to age development has happened rivalry based oninformation. in the world of also make use information to mengefisien academic processes exist indepth. one of [the] applications in education world use information system in course of the academic.elementary school al-muhajirin one of the school not yet use information system in course of theacademic, like student data, teacher data, data matapelajaran, value data. As to the problem not yetused it information system in the academic process, aim from this watchfulness produces academicinformation system. Benefit from watchfulness among others speed up in course of data collection,speed up processing process and data livelihood so that report presentation can on time, produceaccurate data. watchfulness method that used interview method, literature study method, systemsanalysis, system planning, implementation, verification.Result from this watchfulness author can produce elementary school academic informationsystem Al-Muhajirin Barehan Sidoharjo Pacitan. later can useful for the academic process.Keyword: Academic Information System